Pengaruh Substitusi Tepung Kulit Pisang Kepok dan Tepung Bekatul terhadap Mutu Organoleptik Snack Bar sebagai Alternatif Makanan Selingan untuk Remaja Obesitas - Kharisma Dian Natha; Dwi Kurnia PS (Yayasan Literasi Sains Indonesia, 2024)
Obesity results from an imbalance between energy intake and physical activity, influenced by genetic, behavioral, and environmental factors. Poor dietary habits can negatively impact health. One way to address this is by innovating snack products into healthier, such high-fiber snack bars made from a substitution of kepok banana peel flour and rice bran flour. This study aims to assess the organoleptic quality of snack bars as an alternative snack for obese adolescents. A True Experimental Design was employed using Completely Randomized Design with four treatment levels and six replications. The comparison of wheat flour, kepok banana peel flour, and rice bran flour ratios were: P0 (100%:0%:0%), P1 (0%:30%:70%), P2 (0%:50%:50%), and P3 (0%:70%:30%). Statistical analysis was performed using Kruskal-Wallis and Mann-Whitney tests. The results showed organoleptic tests for taste, color, aroma, and texture, the snack bars were well-liked by panelists. The organoleptic analysis for these categories showed significant effect (P Value <0.05). The best treatment, after substituting kepok banana peel and rice bran flour, was found in P1 snack bar. The conclusion of this study is the substitution of kepok banana peel flour and rice bran flour significantly affects the preference level in terms of taste, color, aroma, and texture.